Tingkat Persepsi Petani Padi Sawah terhadap Perubahan Iklim di Desa Banyuasin Kecamatan Riau Silip - Rindiani, Rindiani; Sitorus, Rostiar; Astuti, Rufti Puji (Jurnal Agribisnis, 2023)
This study aims: (1) To describe farmers' perceptions of climate change with lowland rice production in Banyuasin Village (2) To describe the setting of the planting season and management of lowland rice farming in Banyuasin Village from 2018 to 2021. This study started from the preparation stage in the month of 2018 March 2022 until the data collection stage in June 2022 in Banyuasin Village. The method used in this research is a survey method. The sampling technique used in this study is probability sampling with sample selection using proportionate stratified random sampling. Data collection methods used are interviews, questionnaires, and observation. The data analysis method used in this research is the analysis with the perception index. The perception of lowland rice farmers in Banyuasin Village regarding climate change on the indicators of knowledge, attitudes and expectations is considered good. It can be seen that the total value of perception is 60.6 percent. However, the perception of lowland rice farmers on climate change is not good because the knowledge indicator has a score of 58.5 percent and the attitude indicator has a score of 48.5 percent. The timing of planting by farmers is determined by deliberation, namely once a year and the management of lowland rice farming in Banyuasin Village from 2018 to 2021 includes planning, organization, implementation and supervision. Keywords: Paddy, Perception, Farm Management